Cardiovascular and Renal Outcomes with Empagliflozin in Heart Failure - Packer, Milton; Anker, Stefan D; Butler, Javed; Filippatos, Gerasimos; Pocock, Stuart J; Carson, Peter; Januzzi, James; Verma, Subodh; Tsutsui, Hiroyuki; Brueckmann, Martina; Jamal, Waheed; Kimura, Karen; et al. (The New England journal of medicine, 2020)
BACKGROUND: Sodium-glucose cotransporter 2 (SGLT2) inhibitors reduce the risk of hospitalization for heart failure in patients regardless of the presence or absence of diabetes. More evidence is needed regarding the effects of these drugs in patients across the broad spectrum of heart failure, including those with a markedly reduced ejection fraction. METHODS: In this double-blind trial, we randomly assigned 3730 patients with class II, III, or IV heart failure and an ejection fraction of 40% or less to receive empagliflozin (10 mg once daily) or placebo, in addition to recommended therapy. The primary outcome was a composite of cardiovascular death or hospitalization for worsening heart failure. RESULTS: During a median of 16 months, a primary outcome event occurred in 361 of 1863 patients (19.4%) in the empagliflozin group and in 462 of 1867 patients (24.7%) in the placebo group (hazard ratio for cardiovascular death or hospitalization for heart failure, 0.75; 95% confidence interval [CI], 0.65 to 0.86; P<0.001). The effect of empagliflozin on the primary outcome was consistent in patients regardless of the presence or absence of diabetes. The total number of hospitalizations for heart failure was lower in the empagliflozin group than in the placebo group (hazard ratio, 0.70; 95% CI, 0.58 to 0.85; P<0.001). The annual rate of decline in the estimated glomerular filtration rate was slower in the empagliflozin group than in the placebo group (-0.55 vs. -2.28 ml per minute per 1.73 m2 of body-surface area per year, P<0.001), and empagliflozin-treated patients had a lower risk of serious renal outcomes. Uncomplicated genital tract infection was reported more frequently with empagliflozin. CONCLUSIONS: Among patients receiving recommended therapy for heart failure, those in the empagliflozin group had a lower risk of cardiovascular death or hospitalization for heart failure than those in the placebo group, regardless of the presence or absence of diabetes. (Funded by Boehringer Ingelheim and Eli Lilly; EMPEROR-Reduced ClinicalTrials.gov number, NCT03057977.).
Keywords: proporcionální rizikové modely; Stroke Volume; Male; glifloziny; srdeční selhání; Sodium-Glucose Transporter 2 Inhibitors; progrese nemoci; Glomerular Filtration Rate; hospitalizace; Glucosides; Proportional Hazards Models; chronická renální insuficience; Aged; Diabetes Mellitus, Type 2; mužské pohlaví; senioři; tepový objem; Disease Progression; diabetes mellitus 2. typu; benzhydrylové sloučeniny; dvojitá slepá metoda; kardiovaskulární nemoci; lidé; ženské pohlaví; Heart Failure; Humans; Renal Insufficiency, Chronic; Hospitalization; Cardiovascular Diseases; Benzhydryl Compounds; hodnoty glomerulární filtrace; Double-Blind Method; Female; lidé středního věku; glukosidy; Middle Aged